A Clinical Report of Functional and Esthetic Oral Rehabilitation in a High-caries-risk Child: One-year follow-up - Kamila Rosamilia Kantovitz; Anna Maria Cia Papa; Patrícia Almada Sacramento; Maria Beatriz Duarte Gavião; Regina Maria Puppin-Rontani; Fernanda Miori Pascon (Brazilian Dental Science)
This case discusses a multi-disciplinary approach to oral functional and esthetic rehabilitation on a high-caries-risk child with prematurely lost primary teeth due to endodontic complications associated with wide-spread dental caries. The patient was diagnosed with an anterior open bite and atypical swallowing. He exhibited anxiety and low self-esteem due to esthetic impairment. A combination of targeted clinical procedures, a focus on oral home care and active parental involvement was integral to the treatment process. The patient was examined monthly by a pediatric dentist regarding dietary habits, fluoride exposure, biofilm presence, caries prevalence, and malocclusion. Improvement was evident in patient’s masticatory function, facial esthetics, and psychological behavior at a 12-month follow-up evaluation.